PENGARUH REKRUTMEN TERHADAP KINERJA KARYAWAN (Kasus Hotel Resty Menara Pekanbaru) PERIODE 2014 – 2016 - Imam Mukayan; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted at the Hotel Resty Menara Pekanbaru, the study aims to determine the effect of recruitment to employee performance. Recruitment as an independent variable (X). whil the performance of the employee as the dependent variable (Y).Samples are 57 respondent. all emplovees of a Hotel Resty Menara Pekanbaru. data obtained from the questionnaire and further processed to then be tested with statistics through SPSS program. Results of calculation of the coefficient of determination is 0,417. That is to say, the recruitmen affects the performance of employees amounted to 41.7%.Keywords : Recruitment, Employee Performance, Hotel Resty Menara Pekanbaru